Maternal size and body condition predict the amount of post‐fertilization maternal provisioning in matrotrophic fish. Issue 24 (11th December 2018) - Hagmayer, Andres; Furness, Andrew I.; Reznick, David N.; Pollux, Bart J. A.
Abstract: Maternal effects often provide a mechanism for adaptive transgenerational phenotypic plasticity. The maternal phenotype can profoundly influence the potential for such environmentally induced adjustments of the offspring phenotype, causing correlations between offspring and maternal traits. Here, we study potential effects of the maternal phenotype on offspring provisioning prior to and during gestation in the matrotrophic live‐bearing fish species Poeciliopsis retropinna . Specifically, we examine how maternal traits such as body fat, lean mass, and length relate to pre‐ (i.e., allocation to the egg prior to fertilization) and post‐fertilization (i.e., allocation to the embryo during pregnancy) maternal provisioning and how this ultimately affects offspring size and body composition at birth. We show that pre‐ and post‐fertilization maternal provisioning is associated with maternal length and body fat, but not with maternal lean mass. Maternal length is proportionally associated with egg mass at fertilization and offspring mass at birth, notably without changing the ratio of pre‐ to post‐fertilization maternal provisioning. This ratio, referred to as the matrotrophy index (MI), is often used to quantify the level of matrotrophy. By contrast, the proportion of maternal body fat is positively associated with post‐fertilization, but not pre‐fertilization, maternal provisioning and consequently is strongly positively correlated with the MI. We furthermore found that the composition of embryos changes throughout pregnancy. Females invest first in embryo lean mass, and then allocate fat reserves to embryos very late in pregnancy. We argue that this delay in fat allocation may be adaptive, because it delays an unnecessary high reproductive burden to the mother during earlier stages of pregnancy, potentially leading to a more slender body shape and improved locomotor performance. In conclusion, our study suggests that (a) offspring size at birth is a plastic trait that is predicted by both maternal length and body fat, and (b) the MI is a plastic trait that is predicted solely by the proportion of maternal body fat. It herewith provides new insights into the potential maternal causes and consequences of embryo provisioning during pregnancy in matrotrophic live‐bearing species. Abstract : Maternal effects are particularly important, frequently having widespread consequences for offspring phenotype and fitness. Here, we studied potential effects of the maternal phenotype on offspring provisioning prior to and during gestation in the matrotrophic live‐bearing fish species Poeciliopsis retropinna . We show that maternal traits strongly correlate with embryo size and body composition throughout pregnancy. Though, different maternal traits are differently related to pre‐ and post‐fertilization maternal provisioning. We furthermore found that the composition of embryos changes during pregnancy independently of the maternal phenotype.